Reliable preservation methods of mitochondrial DNA analysis for larvae and adult flies of Chrysomya bezziana (Diptera: Calliphoridae). - April H Wardhana; S Muharsini; Suhardono . (Indonesian Center for Animal Research and Development (ICARD), 2003)
The Old World Screwworm fly, Chrysomya bezziana is known as a myiasis agent in Indonesia. The aim of the study is to establish a reliable preservation methods for molecular analysis of insect. Cytochrom b (CB) and Cytochrome Oxidase sub unit I (COI) of mitochondrial DNA were used as markers. Drying method was used to preserve adult flies, while the larvae were kept in 10% formalin and 80% ethanol with or without soaked using hot water prior preservation. Two samples of each preservation were tested. Four primers were used to amplify samples using Polymerase Chain Reaction (PCR). The PCR product were then purified and sequenced. Sequence data analysis of all samples suggested no differences between all preservation methods except using 10% formalin. Preservation samples using 10% formalin is not suitable for collecting mitochondrial DNA of insect. The best methods was using 80% ethanol with killed using hot water prior preservation. This method was able to extract a stabile mitochondrial DNA. Key words: Chrysomya bezziana, preservation, formalin, ethanol, mitochondrial DNA